Soursop Leaf Extract Reduces AST, ALT, Bilirubin Levels, and Liver Damage Scores in Sorafenib-treated Wistar Rats with Hepatocellular Carcinoma - Susilaningsih, Neni; Prajoko, Yan Wisnu; Budijitno, Selamat; Prabowo, Erik; Istiadi, Hermawan; Muniroh, Muflihatul; Riwanto, Ignatius (The Prodia Education and Research Institute (PERI), 2026)
BACKGROUND: Sorafenib, the standard therapeutic agent for advanced hepatocellular carcinoma (HCC), may induce hepatic dysfunction, thereby necessitating adjunctive therapy to mitigate this adverse effect. While preliminary research has suggested that Soursop (Annona muricata) leaves exhibit anti-tumor and hepatoprotective properties, their efficacy in mitigating liver damage associated with sorafenib treatment remains unexplored. This study was conducted to assess the liver-protective effects of soursop leaf extract in Wistar rats receiving sorafenib for HCC treatment.METHODS: Ethanol extract of soursop leaves was prepared using the maceration method. Twenty-nine Wistar rats were divided into five groups: healthy control (HC) group, HCC groups receiving no treatment, sorafenib only, sorafenib + 50 mg/kgBW/day soursop extract, and sorafenib + 100 mg/kgBW/day soursop extract. All groups, except the HC group, were given Diethyl Nitrosamine (DEN) to cause HCC. Following a two-week treatment period, serum levels of aspartate aminotransferase (AST) and alanine aminotransferase (ALT) were assessed using colorimetric methods, while total bilirubin was assessed using diazo with sulphanilic acid method. From histopathological specimen, relative liver weight was measured and liver damage score was assessed using Hematoxylin and Eosin.RESULTS: Administration of sorafenib resulted in a reduction of AST, ALT, total bilirubin, relative liver weight, and liver damage scores. Furthermore, the combined administration of sorafenib with soursop leaf extract at dosages of 50 and 100 mg/kgBW/day led to a dose-dependent amelioration of these indicators. The most pronounced improvement was observed with the highest dose of soursop extract, which significantly reduced AST, ALT, total bilirubin, relative liver weight, and liver damage scores compared to the sorafenib-only group.CONCLUSION: Soursop leaf extract at 100 mg/kgBW/day effectively reduced AST, ALT, bilirubin levels, and liver damage score in sorafenib-treated Wistar rats with HCC, indicating its hepatoprotective effects. These findings suggest that soursop leaf extract may be a promising adjuvant therapy for mitigating sorafenib-induced hepatotoxicity in HCC treatment.KEYWORDS: Annona muricata, hepatocellular carcinoma, sorafenib, AST, ALT, bilirubin, hepatoprotective